The age of Adaline [videorecording (DVD)] - Lively, Blake; Huisman, Michiel, 1981-; Crew, Amanda, 1986-; Ford, Harrison, 1942-; Burstyn, Ellen, 1932- (Lionsgate, 2015)
After miraculously remaining 29 years old for almost eight decades, Adaline Bowman has lived a solitary existence, never allowing herself to get close to anyone who might reveal her secret. But a chance encounter with charismatic philanthropist Ellis Jones reignites her passion for life and romance. When a weekend with his parents threatens to uncover the truth, Adaline makes a decision that will change her life forever.